2004
DOI: 10.1029/2002rs002838
|View full text |Cite
|
Sign up to set email alerts
|

GPS receiver performance characterization under realistic ionospheric phase scintillation environments

Abstract: It is well known that ionospheric scintillation has the potential to affect all types of GPS receivers, even dual‐frequency military precise‐positioning service versions. In a previous effort the degree of degradation to Wide Area Augmentation System (WAAS) operation caused by scintillation, on the basis of simulated data input to an actual WAAS reference receiver under carefully controlled laboratory conditions at Space and Naval Warfare Systems Center, was analyzed and reported [Morrissey et al., 2000]. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…Ledvina et al (2004) have shown that Lband scintillations can form even at mid-latitudes during the main phase of a geomagnetic storm and have suggested that they can also be related to velocity shear and density gradients within the ionosphere. GPS receiver performance with respect to phase scintillation has been investigated by Morrissey et al (2004). GPS scintillation over the European high Arctic during the ionospheric storm of October 2003 has been examined by Mitchell et al (2005), who used a GPS phase and amplitude scintillation receiver located at Ny-Å lesund, Svalbard, Norway.…”
Section: Introductionmentioning
confidence: 99%
“…Ledvina et al (2004) have shown that Lband scintillations can form even at mid-latitudes during the main phase of a geomagnetic storm and have suggested that they can also be related to velocity shear and density gradients within the ionosphere. GPS receiver performance with respect to phase scintillation has been investigated by Morrissey et al (2004). GPS scintillation over the European high Arctic during the ionospheric storm of October 2003 has been examined by Mitchell et al (2005), who used a GPS phase and amplitude scintillation receiver located at Ny-Å lesund, Svalbard, Norway.…”
Section: Introductionmentioning
confidence: 99%
“…Under such conditions, the receiver cannot use the signal from that particular satellite, leading to poorer receiver-satellite geometry. This problem may intensify during solar maximum especially at the low latitudes, when the intensity of scintillation becomes stronger and the signals from a number of satellites may be affected simultaneously (Groves et al 2000;Morrissey et al 2004 and the references therein). Therefore, developing new ionospheric scintillation and receiver tracking models and/or an improvement of existing models are a necessity.…”
Section: Scintillation and Tracking Modellingmentioning
confidence: 99%
“…Several efforts have been made to model the effects of ionospheric scintillation on the PLL performance. These can be summarised as: (i) simulation of time histories passed through software models of tracking loops (Cervera & Knight 1998;Conker et al 2003;Humphreys et al 2005), (ii) evaluation of PLL performance using a Global Positioning System (GPS) signal simulator (Morrissey et al 2004) and (iii) observation of receiver performance during actual events of scintillation in locations of interest (Knight & Finn 1998;Groves et al 2000). Although these approaches have provided some high-level description of the scintillation effects on the PLL performance, they also present some strong limitations if they were to be used to describe the picture completely (Humphreys et al 2009).…”
Section: Scintillation and Tracking Modellingmentioning
confidence: 99%
“…Secondly, with multiple satellites, the ionospheric effect can be measured through many pierce points simultaneously. Single or dual frequency GNSS receivers with configurable carrier tracking loop bandwidth have been traditionally used as Ionospheric scintillation monitors (ISM) [20]. The use of wide carrier loop noise bandwidths can help maintain phase tracking during periods of ionospheric phase scintillation by tracking rapidly changing phase.…”
Section: Introductionmentioning
confidence: 99%
“…The use of wide carrier loop noise bandwidths can help maintain phase tracking during periods of ionospheric phase scintillation by tracking rapidly changing phase. On the other hand, narrow carrier loop noise bandwidth is desirable to tolerate amplitude scintillation with the ability to track at lower C/N 0 conditions, or to "fly-wheel" through the deep fades [20].…”
Section: Introductionmentioning
confidence: 99%